Tiberius’ Germania Strategy - Gökhan Tekir (Journal of Universal History Studies)
Tiberius, whose character and retreat to the island of Capri during his reign’s last decade, tarnished his reputation and caused controversy, actually had a realist and sound Germania strategy. Instead of extending the Roman borders, he chose to protect the Roman frontiers as the new conquests were both costly and dangerous beyond the Rhine. Therefore, he removed his cousin and possible successor Germanicus, who pursued an expansionist and adventurous policy. Although some authors, such as Cassius Dio and Tacitus condemn him relieving his popular and charismatic cousin Germanicus from the command of Germania legions, Tiberius’ this move was justifiable because Germanicus was risking the Roman legions and money for military expeditions, which would boost his popularity rather than the Roman Empire’s security. Tiberius’ considerations in Germania were, on the other hand, upholding the peace and security.